Yes We Can ! - McBratney, Sam and Fuge, Charles (London Penguin Group, 2006)
Little Roo, Quacker Duck and Country Mouse are playing happily together when Little Roo challenges Quacker Duck to jump over a big, big log. Of course he can't and Country Mouse laughs at him. Each friend ends up challenging another to do something they know will be impossible and the three end up quarrelling. It takes Roo's mother to show them that if they celebrate what they can do, instead of laughing at each other, it's much more fun and enjoyable. Can they be friends again? 'Yes we can!'
Include Illustration
Keywords: Kangaroos -- Friendship -- Toleration